Oud neg.nr. 73560-73581. 'Gouda, met o.a. Sonja Meyer, comm. voor Ludieke Stadsvernieuwing' - Haas, Joh. de,
Oud neg.nr. 73560-73581. 'Gouda, met o.a. Sonja Meyer, comm. voor Ludieke Stadsvernieuwing'.